Foreseen impact of climate change on temporary ponds located along a latitudinal gradient in Morocco. Issue 4 (2nd October 2021) - Grillas, Patrick; Rhazi, Laila; Lefebvre, Gaëtan; El Madihi, Mohammed; Poulin, Brigitte
ABSTRACT: Wetlands have been declining worldwide, with an estimated 64–71% loss over the last century. Climate change is increasing pressure on wetlands, affecting their hydrology, and Mediterranean temporary ponds could be particularly vulnerable to these changes. We studied the expected changes in hydrology and plant community according to climatic change scenarios in 18 temporary ponds distributed in 6 areas along a latitudinal and climatic gradient in Morocco (750 km; 4° latitudinal gradient). Richness of pond species was significantly correlated with water level and pond hydroperiod and showed a strong decline from north to south along with increased water stress. Using the Mar-O-Sel software (mar-o-sel.net), we simulated the future evolution of water balance and wetland hydroperiod (duration and frequency of flooding) in these ponds for mid- and late-21st century. Climate projections were estimated based on 2 Representative Concentration Pathway (RCP) scenarios assuming a stabilization (RCP4.5) or increase (RCP8.5) in greenhouse gas emissions. The mean water deficit of the ponds currently ranges between −1380 and −1812 mm/yr and would increase by 16–67% in 2100 under the RCP8.5 scenarios. Pond richness is expected to decrease by 8–15 species in 2100, depending on area, as a result of shorter projected hydroperiods. Severity of change was not related to location of the ponds along the latitudinal (aridity) gradient, but rather to the interaction between the size of their catchment area and the thickness of the permeable soil layer.